Development of polysulfone-surfactant based asymmetric low pressure reverse osmosis membrane for desalination process - Al Dabbaas, Khuzama Mansoor A
Water is important factor for human survival. Living things don't only need water but clean and safe water. However, it is noted that natural water supplies are decreasing as a result of climate change and industrial pollution. To ensure the ustainability of mankind, water conservation and water transport, or construction of new dams, are provided but this has been found to be insufficient to cope with increasing demand in water supply. Based on this, new or alternative mean has to be provided. At present, the most suitable solution is recovery of clean drinking water from salty or sea water which is, by far the most abundant global water resource. To achieve this, desalination has been found to be the effective way. Desalination is a technology that converts saline water into clean water. However, the desalination process is complex in the aspect of operation, maintenance. Due to higher operating pressure, the cost of RO desalination process is estimated 200% higher compare to common water treatment process for water supply. Therefore, the development of a asymmetric low pressure RO membranes for desalination is imperative and critical. In this research, the effect of polymer concentration, type of surfactants (CTAB, Triton X-100 and SDS) and surfactants concentration ranging from 1 wt% to 3 wt% towards the membrane performance, morphology and thermal properties were studied. The RO performances in terms of water flux, saline water flux and salt rejection were investigated. The experiments of saline water were conducted using of varies salt solutions at different concentrations. Scanning electron microscopy(SEM) was used to study the membranes morphologies as well as functional group analysis by using Fourier Transform Infrared (FTIR). Experimental results showed that the optimum surfactant concentration was found to be at 2 wt%. At the optimal point, the fabricated RO low pressure membrane depicted the highest rejection good permeability rate. Experimental data revealed that the addition of surfactant in the asymmetric low pressure RO membrane is not only improved the performance and morphologies of fabricated RO membranes but remarkably lead for better membranes desalination operation at low operating pressure which is very critical for water desalination industry.